Nest box design for a changing climate: The value of improved insulation. (17th January 2018) - Larson, Eliza R.; Eastwood, Justin R.; Buchanan, Katherine L.; Bennett, Andrew T. D.; Berg, Mathew L.
Summary: Mean air temperatures and the frequency, intensity and duration of extreme weather events such as heatwaves are increasing due to climate change. Nest boxes experience more variable and extreme temperatures than natural cavities, which may reduce survival and reproductive success of the species which utilize them, but little is known about the factors which drive nest box temperature profiles. We quantified the potential for retrofitted insulation on nest boxes to modify internal temperatures and to mimic the thermal characteristics of natural cavities more closely. We tested three types of materials with insulative or reflective properties which were easy to retrofit to nest boxes: 3‐cm‐thick polystyrene, pleated foil batts and reflective paint. We found that polystyrene and foil batts reduced mean nest box temperatures during the day by 0.31 ± 0.01°C and 0.17 ± 0.01°C, respectively (but up to 5.84°C and 4.02°C). The effects of all insulation types were dependent on the time of day, and only polystyrene had a significant effect at night, with a greater capacity to retain heat (mean 0.21 ± 0.01°C warmer). Contrary to expectations, reflective paint caused a small increase in temperature during the late afternoon. In our study, the temperature modulation provided by insulation was able to match or exceed that due to variation in nest location and surrounding vegetation canopy cover. Our findings show that polystyrene and foil batts may offer effective and tractable means to mitigate the effects of extreme temperatures in nest boxes and thereby help achieve temperature profiles more similar to natural cavities.